Methodology of Structural and Functional Approach to Management of the Enterprise Economic Safety - DANILOVA, Elvira I.; MARCHENKO, Valentyna M. (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019DO - 10.14505//jarle.v10.2(40).08, 2020)
The relevance of the study is due to the fact that there are several approaches to managing economic security. In this context, the purpose of the article is to generalize existing scientific approaches to managing the economic safety of an enterprise and to investigate their compliance with the objectives of such a management. Moreover, this article aims to analyze the objects of danger in the management of economic security of enterprises. Leading approach to the study of this problem is the comparative method that has afforded revealing peculiarities of the basic concepts of structural-functional access. In the article theoretical generalization of the main provisions of the resource-functional approach are presented. The materials of the paper imply the practical significance for the university teachers of the economic specializations.